GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Mechanistic Insights into Negative Impacts of Heat Stress and the Mitigating Approaches in Legume Crops - Sayantani Basu; Partha Mondal; Y. V. Rao; Jhuma Datta; Rajeev Kumar; Ranjit Singh Gujjar; Mala Kumari; Ramaswamy Manimekalai; Ansheef Ali; Abeer Ali (Journal of Plant Growth Regulation, 2026)

Potential efficacy of repurposed drugs for treating drug-resistant visceral leishmaniasis - Gajala Deethamvali Ghousepeer; Shubhankar Kumar Singh; Shailja Singh; Subhajit Basu; Anjali Priyadarshini; Mansi Rani; Aman Kumar; Niva Singh; V. Samuel Raj; Krishna Pandey; Ramendra Pati Pandey (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Metals exposures and telomere length as a marker of DNA damage among electronic waste workers and a reference group - Mabel Sarpong Duah; Ibrahim Issah; Shirley V. Simpson; Serwaa A. Bawua; Duah Dwomoh; Joseph K. H. Bonney; Shinsaku Inomata; Thomas G. Robins; Niladri Basu; Arima Hiroaki; Julius N. Fobil (Environmental Science and Pollution Research, 2026)

Agroecological cashew cultivation increases pollinator abundance, diversity and flower visitation rates, with potential yield benefits - Iris Berger; Arati Pannure; Ailsa Harris; Parthiba Basu; Barbara M. Smith; Lynn V. Dicks (Agriculture, Ecosystems & Environment, 2026)

Molecular identification and virulence assessment of Metarhizium rileyi isolates against fall armyworm (Spodoptera frugiperda) - Raja Reddy Gundreddy; Basu Sudhakar Reddy; B. V. Jayanth; M. Shashikala; Gouranga Saw; Edula Udaykumar; Deeba Kamil; Fares A. Alzahrani; Rajesh N. Udavant; Suhail Ashraf; Bishwajeet Paul (Archives of Microbiology, 2025)

Uranium exposure and kidney tubule biomarkers in the Multi-Ethnic Study of Atherosclerosis (MESA) - William A. Anderson; Arce Domingo-Relloso; Marta Galvez-Fernandez; Kathrin Schilling; Ronald A. Glabonjat; Anirban Basu; Anne E. Nigra; Orlando M. Gutierrez; Rebecca Scherzer; Jeff Goldsmith; Mark J. Sarnak; Joseph V. Bonventre; et al. (Environmental Research, 2025)

Chandrayaan-3 landing site evolution by South Pole-Aitken basin and other impact craters - S. Vijayan; K.B. Kimi; Anil Chavan; R. Aditi; U. Thahira; V. Rama Subramanian; Rishitosh K. Sinha; Amitabh; Santosh Vadawale; M. Shanmugam; N.P.S. Mithun; Arpit R. Patel; et al. (Icarus, 2025)

Pesticide impacts on insect pollinators: Current knowledge and future research challenges - P. Basu; H.T. Ngo; M.A. Aizen; L.A. Garibaldi; B. Gemmill-Herren; V. Imperatriz-Fonseca; A.M. Klein; S.G. Potts; C.L. Seymour; A.J. Vanbergen (Science of The Total Environment, 2024)

Exploring binding mode assessment of novel kaempferol, resveratrol, and quercetin derivatives with PPAR-α as potent drug candidates against cancer - Sangeeta Ballav; Kiran Bharat Lokhande; Rohit Singh Yadav; Payel Ghosh; K. V. Swamy; Soumya Basu (Molecular Diversity, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Management of tannery waste effluents towards the reclamation of clean water using an integrated membrane system: A state-of-the-art review - Ramesh Kumar; Aradhana Basu; Bhaskar Bishayee; Rishya Prava Chatterjee; Meeraambika Behera; Wei Lun Ang; Parimal Pal; Maulin Shah; Suraj K. Tripathy; Selvaraj Ambika; V. Aruna Janani; Sankha Chakrabortty; et al. (Environmental Research, 2023)

Variation of salinity in the Sundarbans Estuarine System during the Equinoctial Spring tidal phase of March 2011 - Meenakshi Chatterjee; D Shankar; V Vijith; G K Sen; D Sundar; G S Michael; P Amol; Abhisek Chatterjee; P Sanyal; Siddhartha Chatterjee; Anwesha Basu; Saranya Chakraborti; et al. (Journal of Earth System Science, 2021)

Understanding Mechanisms of Food Effect and Developing Reliable PBPK Models Using a Middle-out Approach - Xavier J. H. Pepin; James E. Huckle; Ravindra V. Alluri; Sumit Basu; Stephanie Dodd; Neil Parrott; Arian Emami Riedmaier (The AAPS Journal, 2021)

Rice-specific Argonaute 17 controls reproductive growth and yield-associated phenotypes - Kannan Pachamuthu; Chenna Swetha; Debjani Basu; Soumita Das; Indira Singh; Vivek Hari Sundar; T. N. Sujith; Padubidri V. Shivaprasad (Plant Molecular Biology, 2021)

Genome-wide cis-regulatory signatures for modulation of agronomic traits as exemplified by drought yield index (DYI) in chickpea - Akash Sharma; Udita Basu; Naveen Malik; Anurag Daware; Virevol Thakro; Laxmi Narnoliya; Deepak Bajaj; Shailesh Tripathi; V. S. Hegde; Hari D. Upadhyaya; Akhilesh K. Tyagi; Swarup K. Parida (Functional & Integrative Genomics, 2019)

CLAVATA signaling pathway genes modulating flowering time and flower number in chickpea - Udita Basu; Laxmi Narnoliya; Rishi Srivastava; Akash Sharma; Deepak Bajaj; Anurag Daware; Virevol Thakro; Naveen Malik; Hari D. Upadhyaya; Shailesh Tripathi; V. S. Hegde; Akhilesh K. Tyagi; et al. (Theoretical and Applied Genetics, 2019)

Impact of SARAL/AltiKa-Derived Sea Level Anomaly in a Data Assimilative Ocean Prediction System for the Indian Ocean - Smitha Ratheesh; Rashmi Sharma; K. V. S. R. Prasad; Sujit Basu (Marine Geodesy, 2015)

Synthesis and characterization of silica microsphere and their application in removal of uranium and thorium from water - H. Basu; R. K. Singhal; M. V. Pimple; A. V. R. Reddy (International Journal of Environmental Science and Technology, 2015)

Arsenic Removal from Groundwater by Goethite Impregnated Calcium Alginate Beads - H. Basu; R. K. Singhal; M. V. Pimple; A. V. R. Reddy (Water, Air, & Soil Pollution, 2015)

Optically transparent polymer devices for in situ assessment of cell electroporation - Amit Kumar Majhi; Greeshma Thrivikraman; Bikramjit Basu; V. Venkataraman (European Biophysics Journal, 2015)

Multi‐site downscaling of maximum and minimum daily temperature using support vector machine - V. V. Srinivas; Bidroha Basu; D. Nagesh Kumar; Sanjay K. Jain (International Journal of Climatology, 2014)
Climate change impact assessment studies involve downscaling large‐scale atmospheric predictor variables ( LSAPVs ) simulated by general circulation models ( GCMs ) to site‐scale meteorological variables. This article presents a least‐square support vector machine ( LS‐SVM )‐based methodology for multi‐site downscaling of maximum and minimum daily temperature series. The methodology involves (1) delineation of sites in the study area into clusters based on correlation structure of predictands, (2) downscaling LSAPVs to monthly time series of predictands at a representative site identified in each of the clusters, (3) translation of the downscaled information in each cluster from the representative site to that at other sites using LS‐SVM inter‐site regression relationships, and (4) disaggregation of the information at each site from monthly to daily time scale using k ‐nearest neighbour disaggregation methodology. Effectiveness of the methodology is demonstrated by application to data pertaining to four sites in the catchment of Beas river basin, India. Simulations of Canadian coupled global climate model ( CGCM3 .1/ T63 ) for four IPCC SRES scenarios namely A1B , A2 , B1 and COMMIT were downscaled to future projections of the predictands in the study area. Comparison of results with those based on recently proposed multivariate multiple linear regression ( MMLR ) based downscaling method and multi‐site multivariate statistical downscaling ( MMSD ) method indicate that the proposed method is promising and it can be considered as a feasible choice in statistical downscaling studies. The performance of the method in downscaling daily minimum temperature was found to be better when compared with that in downscaling daily maximum temperature. Results indicate an increase in annual average maximum and minimum temperatures at all the sites for A1B , A2 and B1 scenarios. The projected increment is high for A2 scenario, and it is followed by that for A1B , B1 and COMMIT scenarios. Projections, in general, indicated an increase in mean monthly maximum and minimum temperatures during January to February and October to December.

Improvements in medium range weather forecasting system of India - V S PRASAD; SAJI MOHANDAS; SURYA KANTI DUTTA; M DAS GUPTA; G R IYENGAR; E N RAJAGOPAL; SWATI BASU (Journal of Earth System Science, 2014)

Motor planning ability is not related to lesion side or functional manual ability in children with hemiplegic cerebral palsy - E. V. Kirkpatrick; J. E. Pearse; J. A. Eyre; A. P. Basu (Experimental Brain Research, 2013)

Tidal variations in the Sundarbans Estuarine System, India - MEENAKSHI CHATTERJEE; D SHANKAR; G K SEN; P SANYAL; D SUNDAR; G S MICHAEL; ABHISEK CHATTERJEE; P AMOL; DEBABRATA MUKHERJEE; K SUPRIT; A MUKHERJEE; V VIJITH; et al. (Journal of Earth System Science, 2013)

Synthesis and Characterization of Alumina Impregnated Alginate Beads for Fluoride Removal from Potable Water - H. Basu; R. K. Singhal; M. V. Pimple; A. V. R. Reddy (Water, Air, & Soil Pollution, 2013)

Evaluation of OSCAR ocean surface current product in the tropical Indian Ocean using in situ data - RAJESH SIKHAKOLLI; RASHMI SHARMA; SUJIT BASU; B S GOHIL; ABHIJIT SARKAR; K V S R PRASAD (Journal of Earth System Science, 2013)

Advanced glycation end products enhance reactive oxygen and nitrogen species generation in neutrophils in vitro - Savita Bansal; Manushi Siddarth; Diwesh Chawla; Basu D. Banerjee; S. V. Madhu; Ashok K. Tripathi (Molecular and Cellular Biochemistry, 2012)

Stochastic modeling of the neuronal activity in the subthalamic nucleus and model parameter identification from Parkinson patient data - Ishita Basu; Daniel Graupe; Daniela Tuninetti; Konstantin V. Slavin (Biological Cybernetics, 2010)

Evaluation of wild Arachis species for abiotic stress tolerance: I. Thermal stress and leaf water relations - P. C. Nautiyal; K. Rajgopal; P. V. Zala; Dipti S. Pujari; Manojit Basu; Bhuwaneshwariba A. Dhadhal; Bharat M. Nandre (Euphytica, 2008)

Variation of coastal atmospheric boundary layer characteristics with convective activity along the west coast of India during the Arabian Sea Monsoon Experiment (ARMEX) 2002 - N. V. Sam; U. C. Mohanty; A. Routray; S. Basu (Natural Hazards, 2007)

Experimental superensemble forecasts of tropical cyclones over the Bay of Bengal - T. S. V. Vijaya Kumar; J. Sanjay; B. K. Basu; A. K. Mitra; D. V. Bhaskar Rao; O. P. Sharma; P. K. Pal; T. N. Krishnamurti (Natural Hazards, 2007)

Toward intelligent decision support for pharmaceutical product development - Chunhua Zhao; Ankur Jain; Leaelaf Hailemariam; Pradeep Suresh; Pavankumar Akkisetty; Girish Joglekar; Venkat Venkatasubramanian; Gintaras V. Reklaitis; Ken Morris; Prabir Basu (Journal of Pharmaceutical Innovation, 2006)

Understanding critical material properties for solid dosage form design - Anthony J. Hlinak; Kamal Kuriyan; Kenneth R. Morris; Gintaras V. Reklaitis; Prabir K. Basu (Journal of Pharmaceutical Innovation, 2006)

Studies of the carbohydrate-carbohydrate interaction between lactose and GM3 using Langmuir monolayers and glycolipid micelles - Paul V. Santacroce; Amit Basu (Glycoconjugate Journal, 2004)

Numerical simulation of the marine boundary layer characteristics over the Bay of Bengal as revealed by BOBMEX-98 Pilot experiment - A. N. V. Satyanarayana; U. C. Mohanty; N. V. Sam; Swati Basu; V. N. Lykossov (Journal of Earth System Science, 2000)

Development and Utility of Anti-PepTl Anti-Peptide Polyclonal Antibodies - Sujit K. Basu; Jie Shen; Katharina J. Elbert; Curtis T. Okamoto; Vincent H. L. Lee; Hermann v. Grafenstein (Pharmaceutical Research, 1998)